Post-Error Adjustments - Danielmeier, Claudia; Ullsperger, Markus (Frontiers in Psychology, 2011)
When our brain detects an error, this process changes how we react on ensuing trials. People show post-error adaptations, potentially to improve their performance in the near future. At least three types of behavioral post-error adjustments have been observed. These are post-error slowing (PES), post-error reduction of interference (PERI), and post-error improvement in accuracy (PIA). Apart from these behavioral changes, post-error adaptations have also been observed on a neuronal level with functional magnetic resonance imaging and electroencephalography. Neuronal post-error adaptations comprise activity increase in task-relevant brain areas, activity decrease in distracter-encoding brain areas, activity modulations in the motor system, and mid-frontal theta power increases. Here, we review the current literature with respect to these post-error adjustments, discuss under which circumstances these adjustments can be observed, and whether the different types of adjustments are linked to each other. We also evaluate different approaches for explaining the functional role of post-error slowing. In addition, we report reanalyzed and follow-up data from a flanker task and a moving dots interference task showing 1) that PES and PIA are not necessarily correlated, 2) that PES depends on the response-stimulus interval, and 3) that PES is reliable on a within-subject level over periods as long as several months.